Early access provision: Awareness, educational needs and opportunities to improve oncology patients’ access to care - Krendyukov, Andriy; Singhvi, Sanjay; Green-Morrison, Yianick; Zabransky, Markus (Frontiers in Oncology, 2022)
Early access provision (EAP) is endorsed by competent authorities to improve patient access to innovative medicinal products (InMPs). On-line, fully anonymous survey reaching out to more than 3,258 physicians (including practicing oncologists) was initiated between November 2020 - January 2021. Survey results indicated 75% of respondents were ‘very comfortable’ or ‘comfortable’ with using EAP for their patients, but only 54.5% correctly answered the specific knowledge-based question. For 56% of respondents, experience with EAP in daily practice was very limited. Two-thirds indicated an average or lower level of understanding about the application process and regulatory requirements involved (65.2% and 66.0%, respectively). Knowledge on data collection and serious adverse event reporting under EAP was lower at 57.8% and 50.5% of respondents, respectively. Awareness of physician responsibilities was high in 59.7% of respondents, but fewer understood roles and responsibilities of manufacturing companies (31.2%). Most responders would consider clinical efficacy and safety data from comparative phase III controlled trials as of high importance to support decision to apply for EAP (93.4% and 86.8%, respectively). During the COVID-19 pandemic, the majority of respondents highlighted the need to improve and adapt EAP with regard to the application process and documentation (83.8%), InMP supply and logistics (88.4), and safety reporting process (78.0%). Use of EAP in daily practice remains limited. Challenges posed by the EAP process, together with a lack of education on this topic, might contribute to its under-utilization and influence access of oncology patients to care.